Contextualization Of The Law Responsibility To Filial Elderly Parents In Muslim Families, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this study is to describe the contextualization of filial piety to elderly parents in Muslim families in Indonesia. The research method used is normative sociology. This type of research is Field research. Informants in this study were social care workers, parents who lived in social institutions, and children of parents who were entrusted with care. Based on the results of the study it can be concluded that 1) Older parents who live alone are assisted by neighbors and some are abandoned on the streets so that they are assisted by the surrounding community and placed in social institutions. The reasons for parental care are; changes in family structure, socialization of the elderly, not wanting to bother children, and problems in the family. 2) Children who have left their parents in a social institution and their parents have mutually agreed to the care, the majority of children also often visit their parents and almost all parents feel happy living and being cared for in a social institution.